Age at first exposure to violence and later mental health outcomes: A sex-disaggregated, multi-country analysis in sub-Saharan Africa. (March 2022) - Seff, Ilana; Rodriguez, Deidi Olaya; Meinhart, Melissa; Colarelli, Jonathan; Vahedi, Luissa; Stark, Lindsay
Abstract: Background: A growing body of research has begun examining the relationship between a child's age at first exposure to violence and outcomes of mental wellbeing, though no studies have assessed these relationships in the sub-Saharan African (SSA) region. Objective: Given known gender and sex differences in violence exposure and mental health symptomology, this study conducts a multi-country, gender-stratified analysis of the relationship between age at first incident of physical violence and outcomes of wellbeing in SSA. Participants and setting: This study uses data from the Violence Against Children Surveys on 13–24-year-old males and females in five SSA countries (Kenya (2010), Malawi (2013), Nigeria (2014), Tanzania (2009), and Uganda (2015)). Methods: The predictor of interest is a categorical variable indicating whether a respondent's first exposure to physical violence took place from 0 to 5, 6–11, 12 and older, or never. Outcomes of interest include: sadness, anxiety, suicide ideation, smoking, drug use, and alcohol use. Employing both country-specific and pooled data, gender-stratified, multiple logistic regressions are used to estimate the effect of age at first exposure to physical violence on the six outcomes of interest. Results: Findings show significant variation across countries in age at first exposure to physical violence. For females, findings reveal no association between age at first exposure and outcomes of wellbeing; all periods were equally associated with poor outcomes. For males, results show increased likelihood of anxiety, suicide ideation, and alcohol use when the first violence exposure occurred from 0 to 5 years. Conclusions: This study advances the literature on gender and sex differences in mental health symptomology, suggesting that boys and girls may exhibit different symptomology in response to comparable exposures to violence.